Assessing Democracy In Vitro, In Vivo, and In Actu and the Role of Democratic Theory Today. Issue 2 (1st December 2019) - Deligiaouri, Anastasia; Suiter, Jane
Abstract : How can we define democracy today given the continuous changes that modern societies are undergoing? What is the role of a democratic theorist? This paper articulates a threefold argument in responding to these questions by analyzing the term of democracy in vitro, in vivo, and in actu. The first step is to secure a democratic minimum and the core principles of democracy. The second step involves studying democracy as an ongoing project and examining how the principles of this democratic minimum are encoded. In the third step we deploy the basic premises of discourse theory of Laclau and Mouffe when evaluating a specific discourse of democracy, as this approach encompasses both discursive and nondiscursive practices. Utilizing this three-level evaluative framework for democratic theory will allow us to not only articulate normative principles but also evaluate them according to their mode of implementation.